Website Design For The Executive Body Of The Faculty Of Computer Science Students - hanafi, Ahmad (JUSS (Jurnal Sains dan Sistem Informasi), 2024)
In the current era of globalization, technology is developing very rapidly, in various fields, especially in the information field. But not all activities in a campus / organization are published, the lack of information delivery of each event / other activities so that many do not know. Based on this the author will build a website system that serves to notify about the activities in the Computer Science Faculty BEM. The method used by researchers is the waterfall method, the programming language used in building this system is PHP, and the data base used is My SQL. The expected results are in the form of a website system, which contains activities and information, where students can see info that is on campus or at the BEM itself. Keywords: system benefits, website, BEM